COMPARISON OF THE FINANCIAL PERFORMANCE OF REGIONAL GOVERNMENTS IN INDONESIA BEFORE AND DURING THE COVID-19 PANDEMIC: A LITERATURE REVIEW - Yukotan, Noffany; Nindy Ardilla, Imelda; Suyanto, Suyanto; Anggraeni, Dyah; Hikmatur Rohmah, Selly; Alim, Nizarul (Riviera Publishing, 2023)
This journal manuscript is the result of a literature review analyzing approaches to evaluating regional government financial performance in Indonesia before and during the COVID-19 pandemic. This research uses a systematic literature review method with a sample of 20 articles. The results of the analysis show that the independence, efficiency and effectiveness ratios are the main ratios used in evaluating regional government financial performance. The COVID-19 pandemic has had a significant impact on financial performance with the majority of studies recording a decline in performance in 2020, although some cases experienced an increase. Further research is needed to understand the long-term impact of the pandemic on the financial performance of local governments in Indonesia.